Streams and ground waters - Jones, Jeremy Boyd; Mulholland, Patrick J. (Aquatic ecology series., 2000)
Streams around the world flow toward the sea in floodplains. All along this transit, there is exchange of water between the stream itself and the surrounding sediments which form the floodplain. Many chemical, biological, and geological processes occur when water moves back and forth between streams and these flood plain sediments. Streams and Groundwaters focuses on the consequences of water flow between streams, their underlying sediments, and surrounding landscapes. Certain to appeal to anyone interested in stream ecology, the management of stream ecosystems, or landscape ecology, this volume should become a oft-opened reference.